LEXICAL CHOICES AND LEADERSHIP IDEOLOGY IN SELECTED SPEECHES OF OLUSEGUN OBASANJO, 1976-1979 AND 1999-2007 (2012)
Scholarly studies on presidential speeches in Nigeria have concentrated on general pragmatic, stylistic, discourse and rhetorical features of the speeches to the neglect of an investigation of the link between leadership styles and ideology projected through the speeches, thus, preventing a full understanding and logical explanation of their ideological leadership styles. This study focuses on the ideology in the speeches delivered by Olusegun Obasanjo as military head of state and civilian president with a view to identifying the leadership ideology and lexical indices that characterise the ideology. The study adopted Teun van Dijk's Socio-cognitive model and Michael Halliday's Systemic Functional Grammar which respectively account for ideologically driven meaning and linguistic forms. Fifty scripted speeches (33 delivered as civilian president and 17 delivered as military head of state) were purposively selected from the Internet, newspapers and national archives. The lopsidedness in the selection results from the number of years Obasanjo served as civilian president and military head of state. The data were subjected to content analysis.Three leadership ideologies manifested in the speeches from the two terms, namely, authoritarian ideology, reformist ideology and messianic ideology. At the level of authoritarian ideology, antonyms, synonyms, polysemes, hyponyms and lexical collocations that project imposition, direction and restraint are manifested. Reformist ideology is represented by antonymous, synonymous, polysemous and hyponymous lexical items and collocations that depict the model of hope. Messianic ideology is enacted by antonyms, synonyms and collocations that are used to project the model of a deliverer. Imposition, as an authoritarian trait, is realised by lexical indices that portray unity, antagonism, stringent measures, and criticism. Direction is lexicalised through the models of development, peace and servitude. Restraint is lexicalised by the model of restriction, societal ills, self-reliance, togetherness, destruction, responsibility, awfulness, and selflessness. The model of hope is projected through lexical indices related to development, oppression, optimism, commitment, and self-reliance. The model of a deliverer is accounted for by lexical items that project optimism, failure, cynicism and despair. Comparatively, authoritarian ideology is a feature of both military and civilian speeches and shows Obasanjo's resentment for unethical behaviours and undemocratic practices. Reformist ideology is a major characteristic of the civilian speeches and it reveals Obasanjo's claim to proffer solutions to diverse political and socio-economic problems. Messianic ideology is only represented in the civilian speeches and is characterised by lexical indices that project drastic transformation.Obasanjo's ideological engagements, projected through lexical relations and collocations, portray his leadership styles as authoritarian, reformist (both as military head of state and civilian president) and messianic (as civilian president). Thus, lexical choices play significant roles in indexing ideology in his scripted speeches. Future collaborations between linguists, historians, sociologists and political scientists are capable of producing further rewarding results on the leadership ideology evident in his scripted and unscripted speeches.